Failures in Academic Research Assessing the Frequenting of Predatory Journals by Some Nigerian Academics - Bello, Bashir; James, Fadeyi Taofiq (Departemen Sosiologi Universitas Gadjah Mada, 2025)
Academic progress relies on integrity, and researchers must uphold rigorous standards to ensure knowledge advancement and informed decision-making. However, this foundation is threatened by the proliferation of predatory journals, which exploit the pressure to publish and undermine the credibility of scholarly work. For Nigerian academics, this challenge is compounded by limited awareness, institutional pressures, and scarce access to reputable outlets. This study investigates why Nigerian academics frequent predatory journals, exploring their motivations, consequences for research quality, and implications of this practice. Using an exploratory qualitative research design, the study collected data through Key Informant Interviews (KIIs) with selected academics at the Federal University Gusau, Zamfara State, Nigeria. Data generated from the interview were transcribed, and patterns were identified and organized according to the objectives of the research. The data were analyzed through enumeration, categorization, and thematic analysis. The results show that a significant proportion of Nigerian academics have published in predatory journals, driven by pressures to publish and a lack of awareness. The consequences of this practice include the dissemination of unreliable research, damage to academic reputation, and erosion of public trust. The study recommends urgent interventions to address this issue, including education and awareness campaigns, improved access to reputable journals, and stricter quality control measures.